A phase IB study of ipilimumab with peginterferon alfa-2b in patients with unresectable melanoma. Issue 1 (20th December 2016) - Brohl, Andrew S.; Khushalani, Nikhil I.; Eroglu, Zeynep; Markowitz, Joseph; Thapa, Ram; Chen, Y. Ann; Kudchadkar, Ragini; Weber, Jeffrey S.
Abstract : Background: Ipilimumab and peginterferon alfa-2b are established systemic treatment options for melanoma that have distinct mechanisms of action. Given the need for improved therapies for advanced melanoma, we conducted an open-label, single institution, phase Ib study to assess the safety and tolerability of using these two agents in combination. Methods: Study treatment consisted of ipilimumab given every 3 weeks, for a total of four infusions, concurrent with peginterferon alfa-2b administered subcutaneous weekly for a total of 12 weeks. This was followed by maintenance therapy with peginterferon alfa-2b administered subcutaneously weekly for up to 144 additional weeks. The study was designed as a two-stage dose escalation scheme with continuous dose-limiting toxicity monitoring during the induction phase. Results: Thirty one patients received at least 1 dose of study treatment and 30 were assessable for efficacy endpoints. We found that ipilimumab at 3 mg/kg dosing with peginterfeon alfa-2b at 2 μg/kg/week was the maximum tolerated dose of this combination. The incidence of grade 3 drug-related adverse events (AEs) was 45.2%. There were no grade 4/5 AEs. The overall response rate was 40% by immune-related response criteria. Median progression-free survival was 5.9 months. The median overall survival was not reached with at a median follow-up of 35.8 months. Conclusions: We report that the combination of ipilimumab at 3 mg/kg dosing combined with peginterfeon alfa-2b at 2 μg/kg/week demonstrated an acceptable toxicity profile and a promising efficacy signal. Further study of this combination is warranted. Trial registration: ClinicalTrials.gov identifier: NCT01496807, Registered December 19th, 2011.